Pregnant women's diets and fatty acid intake - a study of the frequency of intake of products that are sources of fatty acids among women in the third trimester of pregnancy - Grot, Martina; Grabowska, Kinga; Białek-Dratwa, Agnieszka; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
Background: Polyunsaturated fatty acids, essential for the human body, have several positive functions that affect human health. Pregnancy is a time of particular demand for these acids, especially DHA and EPA, whose sources are mainly oily marine fish. The supply of adequate amounts of these acids conditions the proper development of the fetus, influencing, among other things, the formation of the central nervous system and the development of the child's retina, as well as protecting against premature birth and increasing the child's birth weight. The aim of the study was to assess the frequency of consumption of fish, vegetable oils, and products rich in polyunsaturated fatty acids and evaluate DHA supplementation by pregnant women, as well as to assess knowledge of PFAs, especially DHA and EPA. Material and methods: 210 pregnant women were included in the study. A self-administered and online survey questionnaires were used as the research tool. A database was created using Microsoft Excel. Results: According to the recommended amounts, 2-3 times a week, Marine fish was consumed by only 12.86% of the women surveyed. Regular consumption of ALA-rich products, such as flaxseed, was declared by 10 respondents, while 59.05% of the surveyed women did not consume it at all. The use of DHA acid supplementation during pregnancy was unequivocally declared by 58 women surveyed, representing only ¼ of the women surveyed. Conclusions: The dietary behavior of pregnant women related to fish consumption is not correct, the overall proportion of fish in the diet of the subjects does not cover the recommended amounts. Vegetable oils and products rich in PFAs are not consumed with adequate frequency by pregnant women. DHA supplementation by pregnant women, despite low fish consumption, is underestimated and at a very low level.